Axiological Knowledge in a Knowledge Driven World: Considerations for Organizations - Queralt Prat-i-Pubill (Copenhagen Business School (CBS), 2018)
The purpose of this thesis is to focus in understanding axiological knowledge in knowledge driven societies which survive thanks to the creation of science and technology and new products and services. The considerations of this thesis are critical to organizations and society at large, because as I will show axiological knowledge is key to ensure the survival of human beings in specific survival conditions. Living in a knowledge driven world means the creation of knowledge in organizations is key. Thus axiological knowledge would need to be created to accommodate this need in organizations. Contrary to established beliefs, and although we experience most our behavior as intentional and volitional pertaining to our particular nature, we are constituted, in the form of automatic, evident, “true” interpretations and understandings of the world, through minimal constituent cultural configurations. This axiological knowledge is shaped by collective motivations through the communication of a constituent speech in the form of narratives, stories, myths, rituals and symbols created to ensure survival in specific material conditions. This axiological knowledge provides us with the adequate knowledge to interpret and value the world according to the existing survival conditions. Currently, many approaches aiming to change the axiological conditions, among others, to promote creativity, responsibility, sustainability and ethics in organizations appeal to personal responsibility and goodwill, without consideration of the affect system and the axiological knowledge currently in place. I argue these proposals are unsuccessful because they disregard the latest social sciences research and also because their key assumptions are outdated. These approaches either assume an anthropology of matter and spirit or an anthropology of matter and reason, as well as a mythical epistemology. This thesis is organized as a compendium of four articles structured in two parts dealing with the complexity of the axiological. The first part comprises two articles describing, argumenting and analysing our current axiological world. The second part, introduces and deals with the diverse discursive approaches to managing motivations in management studies, those of narratology, storytelling and rhetorics, and develops linguistic theory to intervene in collectivities by creating axiological knowledge. I argue, that focusing on the axiological knowledge is a pending need that will not be undetected for long in organization studies. The most difficult issue is to avoid current approaches to the axiological and thus to allow for new research to take place. This thesis is a step towards creating the theoretical basis for this research to develop.
hdl:10398/9672
Keywords: 650